2019
DOI: 10.1002/slct.201902461
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of Michael Addition/Retro‐Michael Reaction/Skeletal Rearrangement in the Synthesis of Arylmethylidene Derivatives of Imidazothiazolotriazines

Abstract: Chemo-, regio-and diastereoselective approach to the synthesis of arylmethylideneimidazothiazolotriazines has been developed based on the Michael addition/retro-Michael reaction and Michael addition/retro-Michael reaction/skeletal rear-rangement cascade processes in the reactions of imidazo [4,5-e] thiazolo [3,2-b] [1,2,4]triazines with arylmethylidene derivatives of malononitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Earlier we have demonstrated that imidazo[4,5- e ]thiazolo[3,2- b ]-1,2,4-triazines and their derivatives functionalized at position 6 are capable of undergoing skeletal rearrangements and transformations of the heterocyclic system proceeding by an ANRORC mechanism under the action of KOH in methanol. Thus, 6-oxindolylideneimidazo[4,5- e ]thiazolo[3,2- b ]-1,2,4-triazines are transformed into substituted 2-oxoquinoline-4-carboxylates in the presence of excess KOH [ 20 ] while their 6-arylmethylidene derivatives undergo rearrangement into the corresponding isomeric derivatives of imidazo[4,5- e ]thiazolo[2,3- c ]-1,2,4-triazine [ 18 , 21 ] ( Scheme 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we have demonstrated that imidazo[4,5- e ]thiazolo[3,2- b ]-1,2,4-triazines and their derivatives functionalized at position 6 are capable of undergoing skeletal rearrangements and transformations of the heterocyclic system proceeding by an ANRORC mechanism under the action of KOH in methanol. Thus, 6-oxindolylideneimidazo[4,5- e ]thiazolo[3,2- b ]-1,2,4-triazines are transformed into substituted 2-oxoquinoline-4-carboxylates in the presence of excess KOH [ 20 ] while their 6-arylmethylidene derivatives undergo rearrangement into the corresponding isomeric derivatives of imidazo[4,5- e ]thiazolo[2,3- c ]-1,2,4-triazine [ 18 , 21 ] ( Scheme 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…According to literature data, this reaction proceeds in alcohol solvents in the presence of base. 9,12 Thus, we attempted to convert linear functionalized products 3 into angular heterocycles 6 . Indeed, reflux of the compound 3a bearing two CO 2 Et groups with stoichiometric amount of Et 3 N in methanol led to the rearranged product 6b in 63% yield (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown [24][25][26] that the products of aldol condensation of imidazo [4,5-e]thiazolo [3,2-b]triazines with carbonyl compounds, namely, aromatic aldehydes and isatins, are capable of skeletal rearrangement of the thiazolotriazine system proceeding in methanol upon treatment with KOH and resulting in the corresponding isomeric imidazo [4,5-e]thiazolo [2,3c]triazine derivatives. In this regard, the possibility of prepearing esters 5 with an angular structure on the basis of directed isomerization of linear imidazo [4,5-e]thiazolo [3,2b]triazines 4a-n in basic media has been studied.…”
Section: Resultsmentioning
confidence: 99%